On Negative Information in Deductive Databases - Suchenek, Marek A; Sunderraman, Rajshekhar (Journal of database management, 1990)
An overview of deductive databases with an emphasis on problems related to negative information is presented. The subject is embedded into the wider context of logic programming, exposing certain peculiarities pertinent to treatment of negation in this field.